A framework for understanding managerial responses to supply chain complexity. Issue 6 (8th May 2018) - Turner, Neil; Aitken, James; Bozarth, Cecil
Abstract : Purpose: The purpose of this paper is to examine the nature of supply chain complexity and extend this with literature developed within the project domain. The authors use the lens of ambidexterity (the ability both to exploit and explore) to analyse responses to complexity, since this enables the authors to understand the application of known solutions in conjunction with innovative ones to resolve difficulties. This research also seeks to investigate how managers respond to supply chain complexities that can either be operationally deleterious or strategically beneficial. Design/methodology/approach: The authors develop a descriptive framework based on the project management (PM) literature to understand response options to complexity, and then use interviews with supply chain managers in six organisations to examine the utility of this framework in practice. The authors ask the research question "How do managers in supply chains respond to complexities"? Findings: The case study data show first that managers faced with structural, socio-political, or emergent supply chain complexities use a wide range of responses. Second, over a third of the instances of complexity coded were actually accommodated, rather than reduced, by the study firms, suggesting that adapting to supply chain complexity in certain instances may be strategically appropriate. Third, the lens of ambidexterity allows a more explicit assessment of whether existing PM solutions can be considered or if novel methods are required to address supply chain complexities. Practical implications: The descriptive framework can aid managers in conceptualising and addressing supply chain complexity. Through exploiting current knowledge, managers can lessen the impact of complexity while exploring other innovative approaches to solve new problems and challenges that evolve from complexity growth driven by business strategy. Originality/value: This study addresses a gap in the literature through the development of a framework which provides a structure on ways to address supply chain complexity. The authors evaluate an existing project complexity concept and demonstrate that it is both applicable and valuable in non-project, ongoing operations. The authors then extend it using the lens of ambidexterity, and develop a framework that can support practitioners in analysing and addressing both strategically necessary supply complexities, together with unwanted, negative complexities within the organisation and across the supply chain.